Development of the major arboviral vector Aedes aegypti in urban drain-water and associated pyrethroid insecticide resistance is a potential global health challenge - Surendran, S.N.; Jayadas, T.T.P.; Kokila, S.; Sharanga, S.; Karvannan, K.; Weerarathne, T.C.; Parakrama Karunaratne, S.H.P.; Ramasamy, R. (Parasites & Vectors, 2019)
Background: Aedes aegypti were found developing in the water in open public drains (drain-water, DW) in Jafna city in northern Sri Lanka, a location where the arboviral diseases dengue and chikungunya are endemic. Methods: Susceptibilities to the common insecticides dichlorodiphenyltrichloroethane (DDT), malathion, propoxur, permethrin and deltamethrin and activities of the insecticide-detoxifying enzymes carboxylesterase (EST), glu tathione S-transferase (GST) and monooxygenase (MO) were compared in adult Ae. aegypti developing in DW and fresh water (FW). Results: DW Ae. aegypti were resistant to the pyrethroids deltamethrin and permethrin, while FW Ae. aegypti were susceptible to deltamethrin but possibly resistant to permethrin. Both DW and FW Ae. aegypti were resistant to DDT, malathion and propoxur. Greater pyrethroid resistance in DW Ae. aegypti was consistent with higher GST and MO activities. Conclusions: The results demonstrate the potential for insecticide resistance developing in Ae. aegypti adapted to DW. Urbanization in arboviral disease-endemic countries is characterized by a proliferation of open water drains and therefore the fndings identify a potential new challenge to global health.
Keywords: Aedes aegypti; Arboviral diseases; Drain-water; Global health; Insecticide-detoxifying enzymes; Insecticide resistance; Mosquito vector biology